2020
DOI: 10.31234/osf.io/yb2h8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Perceived Stress Related to the Covid-19 Outbreak through Stable Psychological Traits and Machine Learning Models

Abstract: The unexpected COVID-19 outbreak and subsequent lockdown impositions are having a significant impact on people’s day-to-day life, confronting Western countries with hitherto unknown contagion threats and restrictions on freedoms. Given the serious effects of stress on physical and mental health, the stressful impact of the COVID-19 emergency represents an important public health issue. The present study assessed the stressful impact of the COVID-19 epidemic in Italy, identifying possible mediators of perceived… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 0 publications
9
31
1
5
Order By: Relevance
“…In cases as such one, the mass media serves as a 'social amplification' since they allow people both to learn about the risk message and interpret it (Social Amplification of Risk Framework; Kasperson et al, 1988), hence the mass media amplify or weaken the public's perception of risk (Chong and Choy, 2018;Ali et al, 2019). Our finding might be understood by considering that the real risk and threat perceived by people was the limited sense of predictability and controllability assigned to the whole situation, rather than the virus per se (Flesia et al, 2020). This role played by the mass media has been traced in several health communication studies such as that on Avian flu in Hong Kong and the United States (Fung et al, 2011), 2009 H1N1 flu virus (Oh et al, 2015), bovine spongiform encephalopathy (Paek et al, 2016), or 2015 Middle East Respiratory Syndrome coronavirus in South Korea (Oh et al, 2020).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…In cases as such one, the mass media serves as a 'social amplification' since they allow people both to learn about the risk message and interpret it (Social Amplification of Risk Framework; Kasperson et al, 1988), hence the mass media amplify or weaken the public's perception of risk (Chong and Choy, 2018;Ali et al, 2019). Our finding might be understood by considering that the real risk and threat perceived by people was the limited sense of predictability and controllability assigned to the whole situation, rather than the virus per se (Flesia et al, 2020). This role played by the mass media has been traced in several health communication studies such as that on Avian flu in Hong Kong and the United States (Fung et al, 2011), 2009 H1N1 flu virus (Oh et al, 2015), bovine spongiform encephalopathy (Paek et al, 2016), or 2015 Middle East Respiratory Syndrome coronavirus in South Korea (Oh et al, 2020).…”
Section: Discussionmentioning
confidence: 80%
“…Over the years, the vast majority of literature on risk perception has recommended the inclusion of cognitive, emotional and social dimensions which directly or indirectly characterize and influence people's risk perception (Slovic, 1987(Slovic, , 1999Slovic et al, 2000;Brug et al, 2004;Renn, 2006;Oh et al, 2015Oh et al, , 2020van der Linden, 2015van der Linden, , 2017Flesia et al, 2020). Using data collected during the 2015 Middle Eastern respiratory syndrome (MERS-CoV) outbreak in South Korea, empirical evidence suggested an association between risk perception and level of trust in social organizations (Yang and Cho, 2017).…”
Section: Risk Perception In Emergency Situationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the Covid-19 outbreak has caused a tremendous amount of stress on the general population ( Zhang et al, 2020 ), prior research has identified stable psychological traits, and several circumstances that predict perceived stress under these circumstances ( Flesia et al, 2020 ). People can react to prolonged stress with coping, which can range from functional, such as a healthy lifestyle and seeking support to more dysfunctional, such as withdrawal and substance use (See Figure 1 ).…”
Section: Coping Styles Can Alleviate or Exacerbate Some Of The Side Ementioning
confidence: 99%